The duopoly policy in the Brazilian model of telecommunications reform - Mattos, César (2004)
One of the important characteristics of the Brazilian Model of Telecommunications Reform (BMTR) was the adoption of a duopoly policy, constraining the entry of new players in the wire segment in the transitional phase until free competition in 2002. This policy was also used in the reform experience of the United Kingdom in telecommunications in the 80's. The theoretical explanations behind this kind of policy are not strong enough to justify the duopoly policy in telecommunications. The most plausible idea rests on the prominent role conferred to privatization revenues in the design of the reform as a means of helping the efforts to consolidate price stabilization in the country. We introduce a model with the trade-offs between competition, duplication of fixed costs and privatization revenues. Despite the importance of fixed costs in the objective function of the regulator, we show that the privatization revenue target is the aspect, which justifies the imposition of entry constraints. The British experience shows that the sacrifice of this kind of policy regarding efficiency in the long run can be substantial.